2011
DOI: 10.1094/mpmi-09-10-0221
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Trichoderma Isolates from Tropical Environments Delay Disease Onset and Induce Resistance Against Phytophthora capsici in Hot Pepper Using Multiple Mechanisms

Abstract: Endophytic Trichoderma isolates collected in tropical environments were evaluated for biocontrol activity against Phytophthora capsici in hot pepper (Capsicum annuum). Six isolates were tested for parasitic and antimicrobial activity against P. capsici and for endophytic and induced resistance capabilities in pepper. Isolates DIS 70a, DIS 219b, and DIS 376f were P. capsici parasites, while DIS 70a, DIS 259j, DIS 320c, and DIS 376f metabolites inhibited P. capsici. All six isolates colonized roots but were inef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(95 citation statements)
references
References 70 publications
7
79
0
9
Order By: Relevance
“…Several epiphytic and endophytic Trichoderma species and strains are already being well studied and further recommended as potential biological control agents against phytophatogenic fungi such as Phytophthora capsici in hot pepper [52], Moniliophthora roreri, M. fide, M. perniciosa, and Phytophthora species in cacao trees [43,53]. Trichoderma strains being studied for their potential to control cacao diseases and ameliorate damage caused by abiotic stresses also have an ability to alter cacao gene expression during colonization [43].…”
Section: Endophytic Trichoderma Strains Exhibit High Antifungal Potenmentioning
confidence: 99%
“…Several epiphytic and endophytic Trichoderma species and strains are already being well studied and further recommended as potential biological control agents against phytophatogenic fungi such as Phytophthora capsici in hot pepper [52], Moniliophthora roreri, M. fide, M. perniciosa, and Phytophthora species in cacao trees [43,53]. Trichoderma strains being studied for their potential to control cacao diseases and ameliorate damage caused by abiotic stresses also have an ability to alter cacao gene expression during colonization [43].…”
Section: Endophytic Trichoderma Strains Exhibit High Antifungal Potenmentioning
confidence: 99%
“…This results initially in an induction of resistance mechanisms that wall off the Trichoderma strain and prevent further plant colonization (Harman et al 2004;Yedidia et al 1999). However, a few plants, such as cocoa, respond to such fungi by permitting their ramification throughout their structure, but the strains involved, when applied to other plants, function only as root colonists (Bae et al 2011). The chemical factors that elicit plant responses are numerous and range from hydrophobin-like proteins, peptides, and smaller molecules.…”
mentioning
confidence: 99%
“…The establishment of root colonization and chemical communication by Trichoderma strains strongly affect plant physiology by changing plant gene expression, as documented by several groups (Alfano et al 2007;Bae et al 2011;Djonovic et al 2007;Marra et al 2006;Shoresh and Harman 2008;Shoresh et al 2010). There are several hundred separate plant genes or proteins known whose expression is altered by root colonization by Trichoderma spp.…”
mentioning
confidence: 99%
“…Deoiled cakes of Karanja was next to Mahua cake which supported 36.33 × 10 6 CFUs of T. harzianum and found significantly lower than Mahua cake. Vermicompost which supported 22.33 × 10 6 CFUs was next to the Karanja cake and found significantly lower than all these cakes but higher than FYM. The least population was recorded from FYM (20.00 × 10 6 ) among all the substrates tested.…”
Section: Screening Of Different De-oiled Cakes and Composts For Massmentioning
confidence: 83%
“…Mev and Meena, [4] studied the efficacy of solid and liquid forms of wheat straw, shelled maize cob, biogas slurry, saw dust, molasses and sugarcane mud either alone or in combination as substrate for mass multiplication of T. harzianum and they reported that T. harzianum population increased up to 40 days and then slightly decreased up to 120 days under room temperature [5,6]. These findings are quite in accordance with present findings as during present course of investigation the time interval for population monitoring of T. harzianum was 15 days and it was noticed that up to 30 days the population of T. harzianum was increased but after 45 days onward it was decreased [7].…”
Section: Determination Of Longevity and Viability Of T Harzianum Inimentioning
confidence: 99%